The Pore Characteristics of Geopolymer Foam Concrete and Their Impact on the Compressive Strength and Modulus - Zhang, Zuhua; Wang, Hao (Frontiers in Materials, 2016)
The pore characteristics of GFCs manufactured in the laboratory with 0-16% foam additions were examined using image analysis (IA) and vacuum water saturation techniques. The pore size distribution, pore shape and porosity were obtained. The IA method provides a suitable approach to obtain the information of large pores, which are more important in affecting the compressive strength of GFC. By examining the applicability of the existing models of predicting compressive strength of foam concrete, a modified Ryshkevitch’s model is proposed for GFC, in which only the porosity that is contributed by the pores over a critical diameter (>100 μm) is considered. This “critical void model” is shown to have very satisfying prediction capability in the studied range of porosity. A compression-modulus model for Portland cement concrete is recommended for predicting the compression modulus elasticity of GFC. This study confirms that GFC have similar pore structures and mechanical behavior as those Portland cement foam concrete and can be used alternatively in the industry for the construction and insulation purposes.